REHABILITATION WITH IMPLANT SUPPORTED HYBRID PROSTHESIS - Huțanu Iulia; Streche Carmen; Grămadă Elena; Agop-Forna Doriana; Tirnovan Lorena; Norina Forna (Romanian Journal of Medical and Dental Education)
The aim of this study is to is to systematically review the available literature and and reveal the good potential and the benefits of hybrid prosthesis. Providing an overview of the materials and methods employed, presenting the results and discussions from existing research, and drawing conclusive insights. This review details the procedures involved in the construction of hybrid dentures for more patients with different systemic conditions by using the transfer copings/laboratory analogs, which simulate the implant in the patient’s mouth, intraoral jig verification to check the correct seating of the copings in the patient’s mouth, occlusal rims were fabricated with modeling wax to record the maxillomandibular relationship and jaw relation was recorded and facebow transfer was done using earpiece type of arbitrary facebow. Conclusions Patients frequently find their use of a removable partial denture (RPD) to be insufficient from a functional and aesthetic standpoint. An alternative to fixed dentures (FD) for free-end saddles is a hybrid prosthesis that combines a RPD and FD using precision attachment. In addition, massive bone defect and insufficient soft tissue support were examined. In all patients, implant‑supported hybrid prostheses were successfully performed.